KERUSAKAN ALAM KALIMANTAN TIMUR DI MATA SASTRAWAN LOKAL - Utomo, Imam Budi (Balai Bahasa Jawa Timur, 2014)
This study aims to identify and expose the opinion of local writers of East Kalimantan on various environmental devastations and their causes in East Kalimantan. Using sociology of literature, it can be identified that the writers of East Kalimantan are closely related to and care about their neighborhood environment which is now suffering from devastation. Those writers actually hold a truly crucial role in publicizing that environment may turn into a ?hell? for a human being if it is not well taken care and preserved. This study aims to identify and expose the opinion of local writers of East Kalimantan on various environmental devastations and their causes in East Kalimantan. Using sociology of literature, it can be identified that the writers of East Kalimantan are closely related to and care about their neighborhood environment which is now suffering from devastation. Those writers actually hold a truly crucial role in publicizing that environment may turn into a ?hell? for human being if it is not well taken care and preserved. Key Words: environmental devastation; writers of East Kalimantan; sociology of literature Abstrak: Kajian ini bertujuan untuk mengetahui dan mengungkapkan pandangan sastrawan lokal Kalimantan Timur terhadap berbagai kerusakan alam dan penyebab kerusakan alam di Kalimantan Timur. Dengan menggunakan teori sosiologi sastra dapat diketahui bahwa sastrawan Kalimantan Timur sangat akrab dan peduli dengan lingkungan hidup di sekitar mereka yang pada saat ini tengah mengalami kerusakan. Para sastrawan Kalimantan Timur tersebut sesungguhnya mempunyai peran yang sangat vital dalam mengampanyekan betapa lingkungan hidup dapat menjadi ?neraka? bagi umat manusia jika tidak dipelihara dan dilestarikan.